Sustained Arc expression in adult-generated granule cells. (31st August 2015) - Meconi, Alicia; Lui, Erika; Marrone, Diano F.
Highlights: Granule cells (GCs) of the dentate gyrus have many exceptional characteristics. Among these, GCs uniquely transcribe Arc mRNA for 8 h following a single experience. The DG also shows robust neurogenesis throughout adulthood. Newborn GCs show different biophysical properties. Despite these differences, we confirm that newborn GCs show sustained Arc expression. Abstract: The dentate gyrus (DG) plays a critical role in memory formation and maintenance. Fitting this specialized role, the DG has many unique characteristics. In addition to being one of the few places in which new neurons are continually added in adulthood, the region also shows a unique long-term sustained transcriptional response of the immediate-early gene Arc to sensory input. Although we know that adult-generated granule cells are reliably recruited into behaviorally-driven neuronal network, it remains unknown whether they display robust late-phase sustained transcription in response to activity like their developmentally-generated counterparts. Since this late-phase of transcription is required for enduring plasticity, knowing if sustained transcription appears as soon as these cells are incorporated provides information on their potential for plasticity. To address this question, adult F344 rats were injected with BrdU (50 mg/kg/day for 5 days) and 4 weeks later explored a novel environment. Arc expression in both BrdU− and BrdU+ neurons was determined 0.5 h, 1 h, 2 h, 6 h, 8 h, 12 h, or 24 h following this behavior. Recently-generated granule cells showed a robust sustained Arc expression following a discrete behavioral experience. These data provide information on a potential mechanism to sculpt the representations of events occurring within hours of each other to create uncorrelated representations of episodes despite a highly excitable population of neurons.